Regulation of human immunoglobulin E synthesis in acute graft versus host disease. - Saryan, J A (1983)
Immunoglobulin (Ig) E synthesis was studied in vitro in eight patients who had received transplants of allogeneic bone marrow. Seven of these patients developed acute graft vs. host disease (GVHD) and elevated serum IgE levels, whereas the eighth did not. In vitro synthesis of IgE, but not of IgG, was elevated in cultures of lymphocytes obtained during acute GVHD (17,923 +/- 14,607 pg/10(6) cells) but not in cultures of lymphocytes obtained after resolution of the acute GVHD when the serum IgE had returned to normal (106 +/- 31 pg/10(6) cells). In contrast, lymphocytes from the patient with no acute GVHD, like normal lymphocytes, failed to synthesize IgE in vitro. The increased in vitro IgE synthesis in acute GVHD was suppressed by normal allogeneic lymphocytes and by autologous lymphocytes obtained after the resolution of the acute GVHD, but not by allogeneic lymphocytes obtained from patients undergoing acute GVHD. The deficiency in functional IgE-specific suppressor cells in acute GVHD occurred in the face of normal or increased percentages of circulating T8+ cells, which in normal subjects contain the IgE-specific suppressor cells. In two patients studied, there was evidence of activated IgE-specific, circulating helper T cells. T cells from these two patients, but not normal T cells, secreted spontaneously upon culture in vitro a factor that induced IgE, but not IgG, synthesis by normal B cells. Finally, a survey of 21 bone marrow transplant recipients revealed that acute GVHD was a necessary requirement for the development of elevated serum IgE levels in recipients of bone marrow transplants. These results suggest that acute GVHD is accompanied by an imbalance in IgE-specific immunoregulatory T cells consisting of activated helper T cells and deficient suppressor cells.